MORALITAS TOKOH MINKE DALAM ROMAN TETRALOGI BURU KARYA PRAMOEDYA ANANTA TOER - Wangunati, Gaudensia; Effendy, Chairil; Priyadi, A. Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research is based on the writer's desire to find the minke character of Minke in Roman Tetralogy of Buru by Pramoedya Ananta Toer. The morality depicted in the Tetralogy of Buru is the morality of the Minke character. The general problem described in this study is "How is Minke's morality in Roman Tetralogy of Buru by Pramoedya Ananta Toer"? The particular problem is 1) How does Minke's morality in relation to God in the romance of the Buru Tetralogy by Pramoedya Ananta Toer ?. 2) How is Minke's morality in relation to oneself in the Buru Tetralogy of Pramoedya Ananta Toer's Work ?. 3) How is Minke's morality in relation to his fellow humanity in the romance of Buru's Tetralogy by Pramoedya Ananta Toer ?. 4) How is the implementation of research results on literary learning in schools ?. The focus of this research is the minke morality reflected in the romance of Pramoedya Ananta Toer's Tetralogy of Buru, the theories used in this study are, Character Values, Character Education, What is Self-Existence, Self-Confidence, Ethics and Philosophy Communication.The method used in this research is descriptive method with qualitative research form. The research approach used is the sociology approach of literary works. Technique of collecting data using indirect technique that is literature study technique and documentary study Â Keywords: Morality of Minke Character, Tetralogy of Buru.